An Empirical Analysis of a Process Industry to Explore the Accident Causation Factors: A Case Study of a Textile Mill in Pakistan - Muhammad Ali Bin Manzoor; Salman Hussain; Wasim Ahmad; Mirza Jahanzaib (Journal of Basic & Applied Sciences, 2018)
Industrial revolutions not only improved the general lifestyle of individuals but also brought an increase in the diversity of the manufactured goods. This diversification involved use of advanced technology and complex methods that entailed dangerous conditions. According to international labor organization, occupational accidents cause death of more than two million individuals each year in different industries. Process industries are complex in nature and tend to lead to more accidents. In Pakistan among the process industries, textile mills are the most accident prone industries in recent times. Therefore, an empirical analysis of a textile process industry has been done using structural equation modelling to examine the interactions between the contributory factors of accidents. Results revealed that unsafe acts are a major contributor to human error, equipment error and unsafe environment that in turn lead to the calamities and disasters that can be avoided with proper safety measures in place.